The Problems of Efficiency of a Property Tax in Ukraine (Economic journal of Lesya Ukrainka Volyn National University, 2016)
In the article are determined theoretical generalization property taxation problems; explored fiscal importance of property taxation in Ukraine; analyzed the structure and the dynamics of property tax revenues. The role of property taxes in the formation of local budgets Ukraine are determined. The basic change in the mechanism of taxation of property taxes are considered and identified existing problems of efficiency of their collection. Studied the internationalexperience of taxation of property taxes. Substantiated promising areas of improvement tax property taxes and increase their efficiency.
Keywords: property taxes, real estate property tax, transportation tax, land tax, tax problem, tax efficiency